Gender differences and risk factors for smoking among patients with various psychiatric disorders in Saudi Arabia: a cross-sectional study - Alosaimi, Fahad D. (Int J Ment Health Syst, 2018)
BACKGROUND: The higher prevalence of smoking among psychiatric patients is well established. However, gender-specific associations have rarely been the focus of studies among patients with various psychiatric disorders. The aim of this study was to estimate the gender-specific prevalence of current smoking by psychiatric patients and its association with various psychiatric disorders and the use of psychotropic medications. METHODS: A cross-sectional observational study was performed between July 2012 and June 2014. Patients were recruited from six hospitals located in the five regions of Saudi Arabia. RESULTS: Of the 1193 patients, 402 (33.7%) were current smokers. The incidence of current smoking was much higher among males than females (58.3% versus 6.7%, p < 0.001). In one or both genders, current smoking was associated with marital status, education, family income, residence, obesity, physical activity, substance abuse, inpatient status, previous psychiatric hospitalization, and age at onset of psychiatric illness. In both gender, smoking was higher in patients who had a secondary psychiatric disorder (66.7% versus 37.5%, respectively), those who had a primary psychotic disorder (63.7% versus 12.3%), and those taking antipsychotic medication (64.1% versus 8.3%) but lower in patients who had a primary depressive disorder (40.3% versus 4.3%), those who had a primary anxiety disorder (45.8% versus 0.0%), and those taking antidepressant medications (53.7% versus 3.6%). In a multivariate analysis adjusted for demographic/clinical characteristics and psychiatric disorders, current smoking was independently associated with primary psychotic disorders in females (OR = 3.47, 1.45–8.27, p = 0.005) but not in males. In a multivariate analysis adjusted for demographic/clinical characteristics and psychotropic medications, current smoking was independently associated with antipsychotic medication use in males (OR = 1.79, 1.10–2.93, p = 0.020). Current smoking was strongly associated with substance abuse in both univariate and multivariate analyses. CONCLUSION: The prevalence of current smoking is high with marked gender difference in a large sample of mixed psychiatric patients in Saudi Arabia. Smoking-cessation programs may be urgently needed for these vulnerable patients.